The Implementation Of A Humanistic Islamic Education Curriculum In Developing Students’ Social Intelligence - Rosmiati Ramli; Syawal Syawal; Muhammad Naim (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the implementation of a humanistic-based Islamic Religious Education (IRE) curriculum in developing students’ social intelligence through a literature review approach. Social intelligence has become an essential competency in the twenty-first century due to increasingly complex social interactions influenced by globalization, technological advancement, and cultural diversity. However, IRE learning practices often remain focused on cognitive achievement and religious content mastery, while the development of social competencies receives less attention. This study employed a library research method by reviewing relevant journal articles, books, conference proceedings, and other scholarly publications. Data were analyzed using content analysis, including literature identification, thematic classification, evaluation, and synthesis. The findings reveal five major themes. First, a humanistic-based IRE curriculum shifts learning orientation from knowledge transmission toward the development of social competencies. Second, the internalization of Islamic humanistic values, such as compassion, tolerance, brotherhood, mutual assistance, and social justice, provides a foundation for social intelligence. Third, participatory learning strategies enhance empathy, communication skills, and collaboration. Fourth, authentic social experiences through service-learning and community-based activities strengthen students’ ability to apply Islamic values in real-life contexts. Fifth, the transformation of teachers’ roles from information providers to facilitators, mentors, and role models supports students’ social development. This study contributes conceptually by highlighting the relevance of humanistic educational principles in Islamic Religious Education and their role in fostering social intelligence. The findings suggest that a humanistic-based IRE curriculum can serve as a strategic framework for developing socially responsible, tolerant, empathetic, and religiously committed learners.